A Suggested Training Curriculum and Its Effect on Some Kinematic Variables and Achievement of the Throwing Stage of the Discus Throwing Event - Saadoun, Hussein Mohsen (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to prepare proposed exercises and identify the effect of the proposed training approach to develop some of the mechanical variables for the stage of discus throwing and completion. The fields of research consisted of the human field for the players of the Specialized School to nurture the sporting talent for arena and field games in Maysan Governorate for ages from (14-16 years) to the discus throwing event for the sports year 2020 and the temporal field for the period from 11/16/2019 to 31/31 2020 and the spatial field Maysan Stadium Olympic .Scientific method the researchers used the experimental approach to solve the research problem. Society and sample of the research Choose the research community in the deliberate manner that represented the players of the specialized school to nurture the sporting talent for the arena and field games in Maysan Governorate for ages from (14-16 years) to the discus throwing event for the sports year 2020 AD Their number is (10) players and the number of the sample was (8) players. They were divided into two groups (4) control players (4) experimental players, and two players were excluded due to conducting the reconnaissance experiment on them, and they formed (80%) of the original community. Either the most important conclusions the proposed training curriculum had a clear effect on the variable starting speed of the disc. The most important recommendations, the researchers recommend to Iraqi trainers to rely on effective and modern training methods and to include them in training programs and the need to emphasize the development of kinematic variables during the training of the effectiveness of discus throwing.